Elastic and Inelastic Alpha Transfer in the \(^{16}\)O+\(^{12}\)C Scattering - Phuc, Nguyen Tri Toan; Phuc, Nguyen Hoang; Khoa, Dao Tien (Communications in Physics, 2021)
The elastic scattering cross section measured at energies \(E\lesssim 10\) MeV/nucleon for some light heavy-ion systems having two identical cores like \(^{16}\)O+\(^{12}\)C exhibits an enhanced oscillatory pattern at the backward angles. Such a pattern is known to be due to the transfer of the valence nucleon or cluster between the two identical cores. In particular, the elastic \(α\) transfer has been shown to originate directly from the core-exchange symmetry in the elastic \(^{16}\)O+\(^{12}\)C scattering. Given the strong transition strength of the $2^+_1$ state of $^{12}$C and its large overlap with the $^{16}$O ground state, it is natural to expect a similar \(α\) transfer process (or inelastic \(α\) transfer) to take place in the inelastic \(^{16}\)O+\(^{12}\)C scattering. The present work provides a realistic coupled channel description of the \(α\) transfer in the inelastic \(^{16}\)O+\(^{12}\)C scattering at low energies. Based on the results of the 4 coupled reaction-channels calculation, we show a significant contribution of the \(α\) transfer to the inelastic \(^{16}\)O+\(^{12}\)C scattering cross section at the backward angles. These results suggest that the explicit coupling to the \(α\) transfer channels is crucial in the studies of the elastic and inelastic scattering of a nucleus-nucleus system with the core-exchange symmetry.